Corporate greed: its effect on customer satisfaction, corporate social responsibility and corporate reputation among bank customers. Issue 3 (December 2018) - Caruana, Albert; Vella, Joseph; Konietzny, Jirka; Chircop, Saviour
Abstract Corporate greed has received increasing attention in recent years with various stories hitting the headlines, particularly after the global financial crisis and the ensuing negative attitudes toward banks. Customer satisfaction and corporate social responsibility are known to have a positive effect on corporate reputation among customers, but perceived corporate greed is likely to impede their effect. Corporate greed, customer satisfaction, corporate social responsibility and corporate reputation are considered, and a research model is proposed. Results indicate that the effect of corporate greed is stronger on corporate social responsibility than on customer satisfaction, implying that corporate social responsibility activities may be futile if the company is perceived to be acting greedily by its customers. Thus, perceptions of corporate greed need to be dealt with swiftly, to enable management to enhance the corporate reputation of the firm.